2006
DOI: 10.1007/s00018-005-5457-9
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone-induced oxidative stress

Abstract: Hypermetabolic state in hyperthyroidism is associated with tissue oxidative injury. Available data indicate that hyperthyroid tissues exhibit an increased ROS and RNS production. The increased mitochondrial ROS generation is a side effect of the enhanced level of electron carriers, by which hyperthyroid tissues increase their metabolic capacity. Investigations of antioxidant defence system have returned controversial results. Moreover, other thyroid hormone-linked biochemical changes increase tissue susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
240
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(263 citation statements)
references
References 213 publications
(392 reference statements)
18
240
0
5
Order By: Relevance
“…These observations corroborate with the earlier reports, where free radical scavenging property of PQQ has been highlighted (Misra et al, 2004;Shrivastava et al, 2010).With other two concentrations of PQQ (1 and 5 mg /kg) also, LPO was inhibited in the tissues of all the studied organs, with a significant elevation in SOD and CAT. Some workers suggest that hypothyroidism protects tissues against accelerated lipid peroxidation, although the data concerning oxidation / antioxidation in hypothyroidism are incomplete and contradictory (Isman et al, 2003;Venditti and Di Meo, 2006). In fact, Dariyerli et al, (2004) did not find any change in the content of malondialdehyde in rats with thiamizoleinduced hypothyroidism.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These observations corroborate with the earlier reports, where free radical scavenging property of PQQ has been highlighted (Misra et al, 2004;Shrivastava et al, 2010).With other two concentrations of PQQ (1 and 5 mg /kg) also, LPO was inhibited in the tissues of all the studied organs, with a significant elevation in SOD and CAT. Some workers suggest that hypothyroidism protects tissues against accelerated lipid peroxidation, although the data concerning oxidation / antioxidation in hypothyroidism are incomplete and contradictory (Isman et al, 2003;Venditti and Di Meo, 2006). In fact, Dariyerli et al, (2004) did not find any change in the content of malondialdehyde in rats with thiamizoleinduced hypothyroidism.…”
Section: Discussionmentioning
confidence: 97%
“…Further, thyroid dysfunction is postulated to be closely related to ROS formation, which might account for thyroid hormone-induced tissue damage. It is also known that thyroid dysfunction increases LPO reactions and ROS (Venditti and Di-Meo, 2006;Messarah et al, 2010). LPO is an autocatalytic mechanism leading to oxidative destruction of cellular membranes (Asayama and Kato, 1990 Jena et al 2012), it was thought that the compound may ameliorate hypothyroidism induced oxidative damage also.Because of this presumption and keeping in mind the unavailability of scientific literature on the role of PQQ in the regulation of thyroid dysfunctions, the present study was undertaken to evaluate the role of PQQ, if any , in ameliorating 6-n-propyl-2-thiouracil (PTU) induced oxidative damage in different organs.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier experimental and clinical studies have shown that hyperthyroidism caused both an elevation in the production of free oxygen radicals and an abnormal oxidative status of the organism [4,22]. Rybus-Kalinowska et al [3] reported that the pre-treatment levels of plasma MDA, which was used as an oxidative stress biomarker, were significantly higher in women with hyperthyroidism and that antithyroid therapy led to the normalization of the plasma MDA levels.…”
Section: Discussionmentioning
confidence: 99%
“…In examining antioxidant changes found in hyperthyroid tissues, it needs to be underscored that although thyroid hormone can directly control levels of enzymes with antioxidant activity or regulate scavenger content, antioxidant depletion could not be the cause, but the consequence of the oxidative stress. The effects of thyroid hormone on antioxidant status have been extensively investigated in rat tissues, while a few data concerning other species are available [159].…”
Section: Antioxidant Statusmentioning
confidence: 99%